Newborn Direct or Conjugated Bilirubin Measurements As a Potential Screen for Biliary Atresia. Issue 6 (June 2016) - Harpavat, Sanjiv; Ramraj, Ramya; Finegold, Milton J.; Brandt, Mary L.; Hertel, Paula M.; Fallon, Sara C.; Shepherd, Ross W.; Shneider, Benjamin L.
ABSTRACT: Objectives: Although screening for biliary atresia (BA) is associated with improved outcomes, no screening program currently exists in the United States. In this study, we explore the possibility of a screening strategy based on newborn direct or conjugated bilirubin (DB or CB) measurements. Our objective is to estimate testing's sensitivity and specificity for BA. Methods: Two groups were examined retrospectively. For sensitivity calculations, a BA group consisting of infants born between January 2011 and December 2014, diagnosed with BA, and cared for at a pediatric gastroenterology referral center was examined. For specificity calculations, a non-BA group that comprised of infants born between June 2009 and August 2011 in a hospital with a policy of checking newborn bilirubin concentrations was studied. Results: All 35 infants with newborn DB or CB measurements in the BA group had elevated concentrations, translating to a sensitivity of 100% (95% CI 87.7–100). In the non-BA group, 8936 of 9102 infants had DB concentrations within the laboratory's reference interval, translating to a specificity of 98.2% (95% CI 97.9–98.4). Three methods—calculating direct:total bilirubin ratios, using 99% reference intervals, and repeat testing—changed specificity to different degrees. Conclusions: Newborn DB or CB measurements may have a high sensitivity and specificity for BA. Specificity can be further improved by using 99% reference intervals and/or repeat testing. Our findings can serve as the foundation for larger prospective studies, to determine whether newborn DB or CB measurements can be an effective screening strategy for BA.